Artificial Intelligence Perspectives in Intelligent Systems Proceedings of the 5th Computer Science On-line Conference 2016 (CSOC2016), Vol 1 - Silhavy, Radek; Senkerik, Roman; Oplatkova, Zuzana Kominkova; Silhavy, Petr.; Prokopova, Zdenka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume is based on the research papers presented in the 5th Computer Science On-line Conference. The volume Artificial Intelligence Perspectives in Intelligent Systems presents modern trends and methods to real-world problems, and in particular, exploratory research that describes novel approaches in the field of artificial intelligence. New algorithms in a variety of fields are also presented. The Computer Science On-line Conference (CSOC 2016) is intended to provide an international forum for discussions on the latest research results in all areas related to Computer Science. The addressed topics are the theoretical aspects and applications of Computer Science, Artificial Intelligences, Cybernetics, Automation Control Theory and Software Engineering.
A Classification Schema for the Job Shop Scheduling Problem with Transportation Resources: State-Of-The-Art Review -- Narration Framework of Chinese Ancient Fiction Images in the Digital Environment -- Toward Computing Oriented Representation of Sets -- Simplified Version of White Wine Grape Berries Detector Based on SVM and HOG Features -- Automated Product Design and Development Using Evolutionary Ontology -- Energy Conservation Technique on Multiple Radio Incorporated Smart Phones -- Real Time Tasks Scheduling Optimization Using Quantum Inspired Genetic Algorithms -- Fuzzy Energy Aware Real Time Scheduling Targeting Mono-Processor Embedded Architectures -- Total Tardiness Minimization in a Flow Shop With Blocking Using An Iterated Greedy Algorithm -- A Firefly Algorithm to Solve the Manufacturing Cell Design Problem -- Solving the Manufacturing Cell Design Problem Via Invasive Weed Optimization -- VLSI Placement Problem Based on Ant Colony Optimization Algorithm -- Pattern Recognition on the Basis of Boltzmann Machine Model -- Parallel Genetic Algorithm Based on Fuzzy Controller for Design Problems -- To Scheduling Quality of Sets of Precise Form Which Consist of Tasks of Circular And Hyperbolic Type In Grid Systems -- Exploring Performance of Instance Selection Methods in Text Sentiment Classification -- Placement of Vlsi Fragments Based on A Multilayered Approach -- Genetic Algorithm Approach in Optimizing the Energy Intake for Health Purpose -- Formal Verification and Accelerated Inference -- A Hybrid Approach to Automated Music Composition -- Detection of White Grapes in Natural Environment Using Neural Network as A Classifier -- A Concept of Innovative Speech Interfaces With Augmented Reality and Interactive Systems for Controlling Lifting Devices -- Sentiment Analysis of Customer Reviews Using Robust Hierarchical Bidirectional Recurrent Neural Network -- Binary Image Quality Assessment - A Hybrid Approach Based on Binarization Evaluation Methods -- Biogeography-Based Optimization Algorithm for Solving the Set Covering Problem -- Approaches to Tackle the Nesting Problems -- Lozi Map Generated Initial Population in Analytical Programming -- Comparison of Success Rate of Numerical Weather Prediction Models With Forecasting System of Convective Precipitation -- High Speed, Efficient Area, Low Power Novel Modified Booth Encoder Multiplier for Signed-Unsigned Number -- Mining Customer Behavior in Trial Period of a Web Application Usage - Case Study -- In Search of a Semantic Book Search Engine on the Web: Are we there Yet? -- Automated Design and Optimization of Specific Algebras by Genetic Algorithms -- Hybrid Nature-Inspired Algorithm for Symbol Regression Problem -- Albanian Advertising Keyword Generation and Expansion -- A Beam-Search Approach to the Set Covering Problem -- Generating Fuzzy Rules for Constructing Interpretable Classifier of Diabetes Disease In Bangladesh -- A Semantic Annotation Model for Arabic Normative Provisions -- A Touch Sensitive Keypad Layout forImproved Usability of Smartphones for the Blind and Visually Impaired Persons -- A Nature Inspired Intelligent Water Drop Algorithm and its Application for Solving the Set Covering Problem -- Firefly Algorithm to Solve a Project Scheduling Problem -- A Binary Invasive Weed Optimization Algorithm for the Set Covering Problem -- A Simplified Form of Fuzzy Multiset Finite Automata -- Fireworks Explosion can Solve the Set Covering Problem -- A Bi-Objective Cat Swarm Optimization Algorithm for Set Covering Problem -- An Alternative Solution to the Software Project Scheduling Problem -- A Binary Cat for the Set Covering Problem -- Study on the Time Development of Complex Network for Metaheuristic.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence